1999
DOI: 10.1177/107179199900500406
|View full text |Cite
|
Sign up to set email alerts
|

Academic Health Care: Leadership in Time of Change

Abstract: Executive SummaryHealth care today is between paradigms. This state of fluctuation places extraordinary challenges on leaders of academic health care facilities. New leadership skills are needed to overcome this dilemma. Communicating a vision and persuading others to work toward this ideal is the responsibility of an effective leader. Prevailing over adversities unique to academic medical centers requires strong leadership and stakeholder support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…80,[104][105][106][107][108] This review identified 30 studies addressing EI in leadership education in medicine. Two groups 109,110 have advocated assessing applicants' EI as a criterion for admission to medical school, and Carrothers et al 111 have proposed an implementation plan for doing so.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 99%
“…80,[104][105][106][107][108] This review identified 30 studies addressing EI in leadership education in medicine. Two groups 109,110 have advocated assessing applicants' EI as a criterion for admission to medical school, and Carrothers et al 111 have proposed an implementation plan for doing so.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 99%
“…Political and social changes have provoked a consistent call for a fundamental shift in how universities and other HE institutions are led (Brown, 2001;Davies, Hides, & Casey, 2001;Froeschle & Donahue, 1998;Kulati, 2003) with many commentators suggesting that universities should learn from the private sector with a view to moving toward a more entrepreneurial outlook.…”
Section: The Role Of Leadership and Leadershipmentioning
confidence: 99%
“…This research project has set out through an illustrative case study to address this omission, and to ask what role leadership and leadership development might play in an OD program in Higher Education: "…outside pressures, largely governmental, have increasingly forced universities…to change, in line with social changes in the environment in which they are embedded." (Elton, 1999, p. 207) These changes have provoked a consistent call for a fundamental shift in how universities and other higher education institutions are led (Brown, 2001;Davies et al, 2001;Froeschle and Donahue, 1998;Kulati, 2003), with many commentators suggesting that universities should learn from the private sector with a view to moving towards a more entrepreneurial outlook.…”
Section: Introductionmentioning
confidence: 99%